PENGARUH MOTIVASI TERHADAP KOMPETENSI PEDAGOGIK GURU PAI PASCASERTIFIKASI MTS NEGERI SE-KOTA PALEMBANG TAHUN 2016 - Nur laila (Conciencia, 2018)
This study aims to provide an overview of multicultural approaches to the pedagogic competence of teachers PAI MTs Negeri pascasertifikasi as Palembang City. This research is a quantitative research used is explanatory survey method (explanatory survey method). The sample of 17 teachers of PAI consists of 9 teachers PAI M.Ts Negeri 1 and 8 teachers PAI M.Ts Negeri 2. Techniques of collecting data using tests, questionnaires, documentation. Validity and reliability. Data analysis techniques using descriptive analysis, bivariate analysis, The results showed pedagogical competence of teachers PAI (52.2%), included in the category of being. including high categories of 5 people (29.4%), and low category amounted to 12 people (70.6%). Hypothesis test concluded There is a significant influence of motivation factors on the pedagogic competence of teachers PAI MTs Negeri as Palembang City. Chi Square statistical test results obtained p value = 0.768, while the value of Odds Ratio (OR) obtained by 1,000 with the level of confidence interval 0.903 - 14.153.